Photoactivatable CRISPR-Cas9 for optogenetic genome editing - Nihongaki, Yuta; Kawano, Fuun; Nakajima, Takahiro; Sato, Moritoshi (Nature biotechnology, 2015)
The genome editing activity of CRISPR-Cas9 can be switched on and off by light using split Cas9 fragments fused tophotoinducible dimerization domains. We describe an engineered photoactivatable Cas9 (paCas9) that enables optogenetic control of CRISPR-Cas9 genome editing in human cells. paCas9 consists of split Cas9 fragments and photoinducible dimerization domains named Magnets. In response to blue light irradiation, paCas9 expressed in human embryonic kidney 293T cells induces targeted genome sequence modifications through both nonhomologous end joining and homology-directed repair pathways. Genome editing activity can be switched off simply by extinguishing the light. We also demonstrate activation of paCas9 in spatial patterns determined by the sites of irradiation. Optogenetic control of targeted genome editing should facilitate improved understanding of complex gene networks and could prove useful in biomedical applications.